The first case of neonatal priapism during hypothermia for hypoxic-ischemic encephalopathy and a literature review - Claudia Fanni; Maria Antonietta Marcialis; Maria Cristina Pintus; Cristina Loddo; Vassilios Fanos (BMC, 2018)
Abstract Neonatal priapism is a rare condition with only 26 described cases in literature since 1879. It is defined as a persistent penile erection occurring in the first 28 days of life, lasting at least 4 h that usually happens in the first days (from 2 to 12 days). It is a very different condition compared to the adult one because in newborns it is a relatively benign phenomenon. As a result of this paucity of described cases, classification and management are not well known by most of neonatologists and currently there are no established guidelines for its management. Most cases are idiopathic but other aetiologies are possible (polycythemia, blood transfusion and drugs). We describe our only case, which occurred during hypothermia therapy and review the literature to clarify the best choice in management of this rare entity.